Spatially-confined lithiation–delithiation in highly dense nanocomposite anodes towards advanced lithium-ion batteries1. Issue 5 (6th May 2015) - Jiang, Yinzhu; Li, Yong; Sun, Wenping; Huang, Wei; Liu, Jiabin; Xu, Ben; Jin, Chuanhong; Ma, Tianyu; Wu, Changzheng; Yan, Mi
<x xml:space="preserve">Abstract</x> Spatially-confined electrochemical reactions are firstly realized in a highly dense nanocomposite anode for high performance lithium ion batteries.